Extending the Notion of Home Through the Language of Poetry - Farrah, Kobe City University of Foreign Studies, Japan, David (Asiatic: IIUM Journal of English Language and Literature, 2010)
This essay will offer a personalised, critical consideration of how the notion of â€œhomeâ€, while remaining central to my vision as a poet, has evolved from the provincial to the international to the universal through the medium of landscape. It will accordingly ask the following question: how do we find a way to express ourselves through the features of a landscape we might not initially consider to be â€œhomeâ€, in the language of poetry? In answer to that question, the Japanese concept of â€œshakkeiâ€ or â€œborrowed landscapeâ€ will be explored as it relates to both literary history and the more contemporary concern for the expression and cultivation of the individual self. In particular, the technique of â€œikedoriâ€, or the â€œcapturing aliveâ€ of a landscape will be examined. And finally, this essay will suggest that â€œshakkeiâ€ and poetry are much more than just metaphors for each other. Rather, they are organically and artistically linked mediums through which creative wonder is formalised, personalised and expressed.